2017
DOI: 10.1155/2017/3237543
|View full text |Cite
|
Sign up to set email alerts
|

Technoeconomic Evaluation for an Installed Small-Scale Photovoltaic Power Plant

Abstract: Solar energy production and economic evaluation are analyzed, in this study, by using daily solar radiation and average temperature data which are measured for 3 years in the Osmaniye province in Turkey. Besides, this study utilizes the photovoltaic- (PV-) based grid connected to a power plant which has an installed capacity of 1 MW investment in electricity production. Economic values show that the net present value (NPV), the first economic method in the research, is about 111941 USD, which is greater than z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 18 publications
0
6
1
Order By: Relevance
“…The long-term saving achieved by the solar system studied by (Sanwogou et al 2019) in Togo, (Doudou 2016) in Niger and (Windarta et al 2020) in Indonesia indicates values that are much lower than those generated by scenario 6. As for the studies of Bourahla et al 2019) in Algeria, (Bermeo et al 2021) in Ecuador, (Hanen et al 2018) in Tunisia, (Doudou 2016) in Niger, (Yaniktepe et al 2017) and (Windarta et al 2020) in Indonesia, the authors observed dates that vary between 6 years and 21 years as the return on their investment. These estimates are higher than those shown in this study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The long-term saving achieved by the solar system studied by (Sanwogou et al 2019) in Togo, (Doudou 2016) in Niger and (Windarta et al 2020) in Indonesia indicates values that are much lower than those generated by scenario 6. As for the studies of Bourahla et al 2019) in Algeria, (Bermeo et al 2021) in Ecuador, (Hanen et al 2018) in Tunisia, (Doudou 2016) in Niger, (Yaniktepe et al 2017) and (Windarta et al 2020) in Indonesia, the authors observed dates that vary between 6 years and 21 years as the return on their investment. These estimates are higher than those shown in this study.…”
Section: Discussionmentioning
confidence: 97%
“…The size of the photovoltaic system designed, the installed price per watt, the internal rate of return (IRR) and the net present value (NPV) are the technical-economic parameters evaluated by the authors. Solar energy production and economic evaluation are analysed in the work of (Yaniktepe et al 2017), using daily solar radiation and average temperature data which are measured for three years in Osmaniye province in Turkey. The economic values of the study such as Net Present Value (NPV), Internal Rate of Return (IRR), payback year, and simple payback period were evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, increasing energy consumption has a negative effect on climate change, global warming and the decrease in energy reserves. In many areas, studies are carried out to reduce energy consumption or to use renewable energy sources (Yaniktepe, 2017). In particular, due to the intensive use of cooling systems both in daily life and in industrial facilities and in order to save energy, studies on this area have recently intensified (Özen, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…As a result of this, investments in solar energy for electricity generation are increasing rapidly in recent years with technological advances in solar energy, global climate change, dependence on other countries, and other environmental factors. In this context, photovoltaic (PV), as one of the usages of solar energy application areas, is intensively applied in order to produce electricity [2,3].…”
Section: Introductionmentioning
confidence: 99%